Judgments over time : the interplay of thoughts, feelings, and behaviors - Sanna, Lawrence J.; Chang, Edward C. (Edward Chin-Ho) (OUP E-Books., 2006)
Time pervades every aspect of people's lives. We are all affected by remnants of our pasts, assessments of our presents, and forecasts of our futures. This book aims to bring together the diverse theory and research of a group of scholars whose work relates to people's judgements over time.